Pengaruh Harga, Kepuasan dan Kepercayaan Terhadap Loyalitas Pelanggan Kartu Simpati di Tegalsari Mandala-II Medan - Irma Raudhatul Jannah Pasaribu; Julianto Hutasuhut; Anggia Sari Lubis; Toni Hidayat (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
This study aims to analyze the effect of price, satisfaction and trust on Simpati Card customer loyalty (Case Study of Tegal Sari Mandala II Village, Medan Denai District). Case of Tegal Sari Mandala II Village, Medan Denai District). This type of research is quantitative, with the population being the people of Tegal Sari Mandala II Village, Medan Denai Subdistrict who actively use the Simpati Simpati card at least 1 year of use. The sample size was set at 154 respondents, research instruments using questionnaire with Likert Scale data measurement scale. Data analysis techniques using tests validity, reliability and classical assumptions. To test the hypothesis used multiple linear regression analysis, t test, F test and R2 test and using the SPSS program. by using the help of the SPSS program. Research results, based on multiple regression test obtained a regression equation, namely Y = 1.267 + 0.552 X1 + 0.359 X2 + 0.184 X3. Based on the t test: price partially has a positive and significant effect on customer loyalty. Satisfaction partially has a positive and significant effect on customer loyalty. Trust partially partially has a positive and significant effect on customer loyalty. In the test simultaneously: price, satisfaction and trust have an effect positive and significant effect on customer loyalty. And in the R2 test variable price, satisfaction and trust have a fairly close relationship with customer loyalty (Case Study of Tegal Sari Mandala II Village, Medan Denai District). (Case Study of Tegal Sari Mandala II Village, Medan Denai District)